109k views
2 votes
Explanation/Answer would be appreciated please

Explanation/Answer would be appreciated please-example-1
User Breixo
by
4.9k points

2 Answers

2 votes
(2,7) is the answer
User Crooksey
by
5.6k points
2 votes

Answer: The solution for the system is (2, -7)

Explanation:

Ok, here we have linear relationships.

A linear relationship can be written as:

y = a*x + b

where a is the slope and b is the y-axis intercept.

For a line that passes through the points (x1, y1) and (x2, y2), the slope can be written as:

a = (y2 - y1)/(x2 - x1).

In this case, we have two lines:

ya, that passes through:

(-8, -5) and (-3, -6)

Then the slope is:

a = (-6 - (-5))/(-3 - (-8)) = (-6 + 5)/(-3 + 8) = -1/5

now, knowing one of the points like (-3, - 6) we can find the value of b.

y(x) = (-1/5)*x + b

y(-3) = -6 = (-1/5)*-3 + b

-6 = 3/5 + b

b = -6 - 3/5 = -33/5

then the first line is:

ya = (-1/5)*x -33/5

For the second line, we know that it passes through the points:

(-8, -15) and (-3, -11)

Then the slope is:

a = (-11 - (-15))/(-3 -(-8)) = (-11 + 15)/(-3 + 8) = 4/5

The our line is:

y(x) = (4/5)*x + b

and for b, we do the same as above, using one of the points, for example (-3, -11)

y(-3) = -11 = (4/5)*-3 + b

b = -11 + 12/5 = -(55 + 12)/5 = -43/5

then:

yb = (4/5)*x - 43/5.

Ok, our system of equations is:

ya = (-1/5)*x -33/5

yb = (4/5)*x - 43/5.

To solve this, we suppose ya = yb

then:

(-1/5)*x + -33/5 = (4/5)*x - 43/5.

-33/5 + 43/5 = (4/5)*x + (1/5)*x

10/5 = 2 = (4/5 + 1/5)*x = x

2 = x

now we evaluate x = 2 in one of the lines:

ya = (-1/5)*2 -33/5 = -2/5 - 33/5 = -35/5 = -7

Then the lines intersect at the point (2, - 7), which is the solution for the system.

User Sarath Babu
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.